Exploring Transformative Learning for Student Self-Care in Undergraduate Healthcare Education: An In-Progress Action Research Study - Margaret Schmidt (Adult Education Research Conference, 2024)
This presentation highlights the investigation of an Action Research study focused on undergraduate preparedness for student self-care in healthcare education.
Keywords: healthcare education; student self-care; transformative learning; well-being; burnout; compassion fatigue